Determinants of Willingness to Pay for Health Insurance in Germany—Results of the Population-Based Health Study of the Leipzig Research Centre for Civilization Diseases (LIFE-Adult-Study) - Hajek, André; Enzenbach, Cornelia; Stengler, Katarina; Glaesmer, Heide; Hinz, Andreas; Röhr, Susanne; Stein, Janine; Riedel-Heller, Steffi G.; König, Hans-Helmut (Frontiers in Public Health, 2020)
Objective: To investigate which factors are associated with the willingness to pay (WTP) for health insurance. Methods: The analysis (n=1,248 individuals) is based on data of a large population-based study - the Health Study of the Leipzig Research Centre for Civilization Diseases (LIFE-Adult-Study). With regard to WTP for health insurance, a contingent valuation method with a payment card was used. Several explanatory variables were included. For example, personality factors (in terms of agreeableness, conscientiousness, extraversion, neuroticism, and openness to experience) were assessed using the NEO-16 Adjective Measure. Results: Average WTP for health insurance per month equaled about €240 which corresponds to approximately 14% of household net equivalent income. Multiple regressions showed that an increased WTP was associated with lower age (β=-1.7, p<.001), higher (log) household net equivalent income (β=153.6, p<.001), higher social support (β=2.0, p<.05), and private health insurance (β=131.1, p<.001). Furthermore, an increased WTP for health insurance was associated with higher openness to experience (β=10.1, p<.05), whereas it was not associated with agreeableness, conscientiousness, extraversion, and neuroticism. Conclusion: The quite large amount of average WTP for health insurance may suggest that individuals accept current contributions to health insurances and would probably accept higher contributions. While previous studies mainly focused on individuals in late life, we identified a link between socioeconomic, health-related factors, and personality factors (in terms of openness to experience) and WTP in the general adult population.